PERBANDINGAN PENYULUHAN MEDIA VIDEO DENGAN LEAFLET TERHADAP PENGETAHUAN IBU HAMIL TENTANG TANDA BAHAYA KEHAMILAN DI PUSKESMAS TRUCUK 2, KLATEN - Wahyuni, Sri; Wintoro, Piscolia Dynamurti; Qoyyimah, Anna Uswatun; Angelina, Amanda Putri (INVOLUSI: Jurnal Ilmu Kebidanan, 2024)
Danger signs of pregnancy are signs that indicate danger that occurs during pregnancy. If the danger signs of pregnancy are not detected, it can result in the death of both the baby and the mother. This study aims to determine the level of knowledge of pregnant women about the danger signs of pregnancy before and after being given counseling with video media and leaflets, to find out the comparison of counseling with video media and leaflets about the danger signs of pregnancy, to find out that counseling with video media is better in increasing mother's knowledge. This research method is a quasi-experimental design with a pretest-posttest with control group. The population in this study were 32 pregnant women at the Trucuk 2 Public Health Center Klaten. Sampling using total sampling, the number of samples in this study were 32 pregnant women who came during the counceling which were divided into 2 groups, the experimental group of 16 pregnant women and the control group of 16 pregnant women. The instrument used in this research is a questionnaire. The results of this study were analyzed using the T-Paired Test, the results obtained p-value (0.031 <0.05), meaning that there is a significant difference between video media and leaflets. The conclusion of this study is the knowledge of pregnant women before and after being given video media and leaflets has increased, there is a significant difference between video media and leaflets, video media is better in increasing knowledge. Suggestions from this study are to provide information and education to pregnant women using interesting video media about the danger signs of pregnancy.